Blood‐Brain–Barrier Microvasculatures: Modeling Nanocarrier Transport across a 3D In Vitro Human Blood‐Brain–Barrier Microvasculature (Adv. Healthcare Mater. 7/2020). Issue 7 (8th April 2020) - Lee, Sharon Wei Ling; Campisi, Marco; Osaki, Tatsuya; Possenti, Luca; Mattu, Clara; Adriani, Giulia; Kamm, Roger Dale; Chiono, Valeria
Abstract : The cover image shows the potentiality of an in vitro microfluidic 3D model of a human blood‐brain–barrier microvasculature as a tool to assess the permeability of nanoparticles, surface functionalized with specific ligands, and their spatio‐temporal distribution into brain tissue. This work is found in article number 1901486 by Roger Dale Kamm, Valeria Chiono, and co‐workers.